Customer Satisfaction Index of Singapore 2013: Q1 Results - Institute of Service Excellence, SMU (Institutional Knowledge at Singapore Management University, 2013)
The Customer Satisfaction Index of Singapore (CSISG) computes customer satisfaction scores at the national, sector, sub-sector, and company levels. The CSISG serves as a quantitative benchmark of the quality of goods and services produced by the Singapore economy over time and across countries. This set of Q1 results begins the CSISG’s seventh year of measurement.